Somatic mutations in tumor-infiltrating lymphocytes impact on antitumor immunity - Mukohara, Fumiaki; Iwata, Kazuma; Ishino, Takamasa; Inozume, Takashi; Nagasaki, Joji; Ueda, Youki; Suzawa, Ken; Ueno, Toshihide; Ikeda, Hideki; Kawase, Katsushige; Saeki, Yuka; Kawashima, Shusuke; et al. (Proceedings of the National Academy of Sciences, 2024)
Immune checkpoint inhibitors (ICIs) exert clinical efficacy against various types of cancers by reinvigorating exhausted CD8 + T cells that can expand and directly attack cancer cells (cancer-specific T cells) among tumor-infiltrating lymphocytes (TILs). Although some reports have identified somatic mutations in TILs, their effect on antitumor immunity remains unclear. In this study, we successfully established 18 cancer-specific T cell clones, which have an exhaustion phenotype, from the TILs of four patients with melanoma. We conducted whole-genome sequencing for these T cell clones and identified various somatic mutations in them with high clonality. Among the somatic mutations, an SH2D2A loss-of-function frameshift mutation and TNFAIP3 deletion could activate T cell effector functions in vitro. Furthermore, we generated CD8 + T cell–specific Tnfaip3 knockout mice and showed that Tnfaip3 function loss in CD8 + T cell increased antitumor immunity, leading to remarkable response to PD-1 blockade in vivo. In addition, we analyzed bulk CD3 + T cells from TILs in additional 12 patients and identified an SH2D2A mutation in one patient through amplicon sequencing. These findings suggest that somatic mutations in TILs can affect antitumor immunity and suggest unique biomarkers and therapeutic targets.